Clinicopathological correlation of cancer stem cell markers Oct-4 and CD133 expression as prognostic factor in malignant lesions of gallbladder: An immunohistochemical study - Naseem Fatima; Anand Narain Srivastava; Jaya Nigam; Nishi Tandon; Rumana Ahmad; Vijay Kumar (Wolters Kluwer Medknow Publications, 2019)
Background: Gallbladder cancer (GBC) is the most frequent biliary tract cancer, with high morbidity and poor prognosis, and shows early metastasis and invasiveness. No reliable biomarkers are available for detection of GBC progression. Aim: To investigate the immunohistochemical expression of Oct-4 and CD133 in malignant and nonneoplastic lesions of gallbladder and to analyze the clinical significance of the expressions related to clinicopathological parameters. Settings and Design: This is a prospective case control study, conducted in medical college background. Materials and Methods: A total of 103 cases of gallbladder were grouped into malignant lesions (n = 48) and nonneoplastic lesions (simple epithelial hyperplasia; n = 35 and chronic cholecystitis; n = 20). All tissue samples were evaluated for expression of Oct-4 and CD133 using immunohistochemistry in an effort to elucidate the correlation between their expressions with clinicopathological parameters. Statistical Analysis: The final score was calculated by multiplying the intensity to the percentage of positive cells. The scores ≥2 were considered as positive. Results: Significant positive correlation of higher expression levels of Oct-4 and CD133 were observed in malignant as compared to nonneoplastic lesions of gallbladder (P < 0.0001). High expression of Oct-4 and CD133 were significantly associated with tumor grading (Oct-4, P = 0.04; CD133, P = 0.02), staging (Oct-4, P = 0.03; CD133, P = 0.02), and liver metastasis (Oct-4, P = 0.01; CD133, P = 0.007). Significantly reduced survival was observed with high expression of Oct-4 (P = 0.002). No significant correction was observed between CD 133 and survival. Conclusion: This study revealed that high expression level of Oct-4 may provide a new insight for the prognosis of the disease in terms of clinical staging and grade.